2015
DOI: 10.1007/978-3-319-15588-3_16
|View full text |Cite
|
Sign up to set email alerts
|

The Atomic Structure of Two-Dimensional Silica

Abstract: Determining the structure of amorphous materials used to be challenging due to the complexity of this material class. Despite many attempts to resolve amorphous materials by various diffraction methods as well as scanning probe methods, no-one has yet been able to carry out atomic imaging and to clearly identify the structure of amouphous materials. Only modern preparation methods in combination with advanced scanning tunneling and atomic force microscopy have succeeded in decrypting the everyday material glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…If the high temperature annealing during the bilayer preparation is continued under 5 × 10 –6 mbar O 2 , the disordered (usually called vitreous) bilayer phase can be obtained, indicated by the transformation of the (2 × 2) superstructure into a ring in LEED and characterized in real space by a range of variable Si ring sizes with a definite size distribution. , Thus, this phase is characterized by a very special, two-dimensional disorder in which the correlation between the two Si–O networks of the BL is fully maintained and the BL becomes disordered only in the plane. Since in this way a realization of the disorder in bulk silica glass, suggested more than 80 years ago by Zachariasen, can be obtained, this is a very interesting process which can be used as a model for disordered silica …”
Section: Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…If the high temperature annealing during the bilayer preparation is continued under 5 × 10 –6 mbar O 2 , the disordered (usually called vitreous) bilayer phase can be obtained, indicated by the transformation of the (2 × 2) superstructure into a ring in LEED and characterized in real space by a range of variable Si ring sizes with a definite size distribution. , Thus, this phase is characterized by a very special, two-dimensional disorder in which the correlation between the two Si–O networks of the BL is fully maintained and the BL becomes disordered only in the plane. Since in this way a realization of the disorder in bulk silica glass, suggested more than 80 years ago by Zachariasen, can be obtained, this is a very interesting process which can be used as a model for disordered silica …”
Section: Results and Interpretationmentioning
confidence: 99%
“…It is counterbalanced by the energy necessary to strain the local chemical bonds in length and angle in the silica layer and/or from it to the Ru, to produce defects. The two phases accommodate the misfit to the Ru periodicity , differently. The rotated ML phase shows a moiré pattern, i.e.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the atomic-level structure of an amorphous silica bilayer grown on Ru(0001) was resolved in real space (Figure ). , This system offers exciting opportunities to probe its structure–reactivity relationships. The silica bilayer is amorphous in the xy -plane (substrate plane), although it is ordered in the z -direction and atomically flat at the surface.…”
Section: Experimental and Computational Approaches In The Investigati...mentioning
confidence: 99%
“…The recently reported epitaxial, solid solution, single-crystalline Ni–Pd alloy films with continuously tunable lattice constant open possibilities to tackle this challenge . This paper focuses on the growth of 2D silicates on transition-metal substrates that have gained interest as 2D analogues of zeolites. It will be shown that silica deposition onto a Ni–Pd alloy substrate in an oxygen-rich environment results in the self-limited growth of a 2D Ni silicate in a dioctahedral clay structure not seen in bulk Ni silicates.…”
Section: Introductionmentioning
confidence: 99%